2018
DOI: 10.17222/mit.2017.213
|View full text |Cite
|
Sign up to set email alerts
|

Role of tool rotational speed in influencing microstructural evolution, residual-stress formation and tensile properties of friction-stir welded AZ80A Mg alloy

Abstract: Joining flat plates of the AZ80A Mg alloy was carried out using the friction-stir-welding technique, employing various speeds of rotation (the tool), and it was observed that an M-shaped distribution characterizes the stress (residual) distributed in the longitudinal direction. Apart from this, the longitudinal stress (tensile) on the advancing side (AS) was found to be larger than that on the retreating side (RS) in the stir zone. It was experimentally recorded that there seem to be a slight increase in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As a result, it can be concluded that increasing the rotational speed of the FSP tool leads to progressively diminishing strength values, which is consistent with that reported by. 27 In addition, delay in the formation of micro-cracks and their propagation is an outcome of uniformity of microstructure which allows dislocation slips to occur easily. 28 Also, FSP caused anisotropy in tensile properties with a higher level of anisotropy in multiple passes.…”
Section: Results and Discussion (Metallurgical)mentioning
confidence: 99%
“…As a result, it can be concluded that increasing the rotational speed of the FSP tool leads to progressively diminishing strength values, which is consistent with that reported by. 27 In addition, delay in the formation of micro-cracks and their propagation is an outcome of uniformity of microstructure which allows dislocation slips to occur easily. 28 Also, FSP caused anisotropy in tensile properties with a higher level of anisotropy in multiple passes.…”
Section: Results and Discussion (Metallurgical)mentioning
confidence: 99%
“…In this experimental research, anticipated peak temperature Tmax was validated against experimentally measured temperature values and found to coincide with one another. Results of experimental runs carried out at the optimised process parameter conditions (i.e, tool rotational speed = 818 rpm; force applied on the FSW tool axially = 3.64 kN; rate of traversing of tool over workpiece = 1.48 mm/s) were taken as the inputs for generating line plots and contours [3,44]. The variations of temperature on the surface of the workpiece w.r.t the offset lines and bonding lines, when the tool approaches the workpiece centre part, for the various employed FSW tools with the different pin geometries are illustrated in the Figure 7 Figure 8 decribes in detail, the generated temperature contour graphs on the top surfce of the work piece and on the bonding surfaces for tools with different pin geometries.…”
Section: Comparison Of Anticipated and Experimental T Maxmentioning
confidence: 99%
“…In this experimental research, anticipated peak temperature Tmax was validated against experimentally measured temperature values and found to coincide with one another. Results of experimental runs carried out at the optimised process parameter conditions (i.e, tool rotational speed = 818 rpm; force applied on the FSW tool axially = 3.64 kN; rate of traversing of tool over workpiece = 1.48 mm/s) were taken as the inputs for generating line plots and contours [3,44]. The variations of temperature on the surface of the workpiece w.r.t the offset lines and bonding lines, when the tool approaches the workpiece centre part, for the various employed FSW tools with the different pin geometries are illustrated in the Figure 7 (a) & (b).…”
Section: Comparison Of Anticipated and Experimental T Maxmentioning
confidence: 99%